(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: ST elevation myocardial infarction (STEMI) is a life-threatening condition that is often due to a thrombotic occlusion of an offending coronary artery. Measuring the degree of stenosis is important for defining risk and choosing a revascularization strategy. Objective: To establish the prevalence and extent of stenosis of culprit coronary arteries in patients with acute STEMI who are treated with primary PCI. Methods: The current study is a cross-sectional descriptive study carried out at the Department of Inpatients of Cardiology, NICVD Karachi, from October 2019 to April 2020. A total of 181 patients with STEMI undergoing primary PCI were included. Quantitative coronary analysis parameters of vessel diameter, lesion length, area stenosis, and diameter stenosis were measured through angiography. Results: Severe Stenosis (>70%) was noted among 60.2% of the patients, moderate stenosis among 26.5% of patients, and minimal stenosis among 13.3%. Severe stenosis was significantly correlated with lower TIMI flow grades and higher thrombus burden. Conclusion: Culprit arteries of STEMI have a predominant angiographic finding of severe stenosis requiring early recognition and intervention.